Is Neonatal Hyperbilirubinemia Exposure Associated with a Risk of Autism Spectrum Disorder? A Nationwide Cohort Study - Hung, Tung-Wei; Tsai, Jeng-Dau; Pan, Hui-Hsien; Chen, Hsuan-Ju; Liao, Pen-Fen; Sheu, Ji-Nan (American Journal of Perinatology, 2020)
Objective This study aimed to determine whether neonatal hyperbilirubinemia is associated with a risk of autism spectrum disorder (ASD) using a large population-based cohort.Study Design This retrospective cohort study used data from the children's database (2000–2012) of the National Health Insurance Research Database (1996–2012) in Taiwan. We included neonates who were born between 2000 and 2004 and aged <1 month diagnosed with and without hyperbilirubinemia. The primary outcome was physician-diagnosed ASD. At the end of 2012, multivariate Cox's regression analysis was used to estimate hazard ratios (HRs).Results A total of 67,017 neonates were included. The neonates with hyperbilirubinemia were associated with 1.28-fold increased risk of ASD (HR = 1.28, 95% confidence interval [CI]: 1.05–1.57) compared with those without hyperbilirubinemia. In subanalysis to determine how phototherapy and exchange transfusion treatment for hyperbilirubinemia were associated with ASD showed no association between treatment and ASD, suggesting the lack of a dose-response effect of hyperbilirubinemia on the risk of ASD. Boys had a nearly six-fold higher risk of ASD than girls (HR = 5.89, 95% CI: 4.41–7.86). Additionally, neonates born with preterm birth and low birth weight were associated with a risk of ASD (HR = 1.46, 95% CI: 1.00–2.13).Conclusion We did not observe a dose-response effect of hyperbilirubinemia on ASD, but neonatal hyperbilirubinemia may be an independent risk factor for ASD if there is a residual confounding by other perinatal complications. Therefore, this study does not support a causal link between neonatal hyperbilirubinemia exposure and the risk of ASD.
Keywords: autism spectrum disorder; neonatal hyperbilirubinemia; risk factor; boy; preterm birth and low birth weight